Applied Bioelectrochemistry: Plastic Degradation and Energy Generation Using Klebsiella oxytoca in Microbial Fuel Cells - Rojas-Flores Segundo; Cabanillas-Chirinos Luis; Nélida Milly Otiniano; Magaly De La Cruz-Noriega; Nancy Soto-Deza; Anibal Alviz-Meza; Ángel Darío González-Delgado (Fermentation, 2025)
Plastic pollution remains a critical global environmental challenge, with conventional disposal methods contributing to ecosystem degradation. Simultaneously, energy scarcity affects numerous rural communities, limiting development opportunities. This study presents an innovative approach that integrates microbial fuel cells (MFCs) with Klebsiella oxytoca to simultaneously degrade plastic waste and generate bioelectricity. The monitoring results over 40 days revealed optimal performance on day 28, with a peak voltage of 0.714 ± 0.026 V and an electric current of 3.149 ± 0.124 mA. The biocatalyst exhibited an electrical conductivity of 140.466 ± 5.180 mS/cm and an oxidation-reduction potential of 109.519 ± 5.35 mV, indicating efficient electron transfer. Furthermore, the MFCs achieved a maximum power density of 11.391 ± 0.814 mW/cm2 with a current density of 5.106 mA/cm2, demonstrating their potential for sustainable energy production. Fourier transform infrared (FTIR) analysis confirmed structural modifications in the plastic, with decreased vibrational peaks indicative of polymer degradation. Additionally, scanning electron microscopy (SEM) micrographs revealed porosity and surface cracks, highlighting Klebsiella oxytoca’s biodegradation capacity. These findings establish the viability of bioelectrochemical systems for simultaneous waste remediation and renewable energy generation, paving the way for scalable applications in environmental biotechnology. By coupling microbial degradation with electricity production, this research supports the development of sustainable solutions aligned with the principles of circular economy and climate change mitigation.